PEMBERDAYAAN KAMPUNG SEHAT KELURAHAN MARGOREJO MELALUI PROGRAM KAMPUNG PENDIDIKAN - KAMPUNGE AREK SUROBOYO - Mega Arisia Dewi (LP2M STP Mataram, 2021)
The village education program - Kampunge Arek Surabaya is one of the programs initiated by the Surabaya City government in creating a village with a community who has awareness and concern to ensure children's growth and development in both spiritual, intellectual, emotional, and physical aspects through an educative village environment, safe, comfortable, friendly, healthy, and creative. One of them is through empowering healthy villages in Margorejo sub-district, Surabaya. The goal of empowering healthy villages in Margorejo Village is to appreciate the spirit of community association in providing guarantees for children's rights so as to make children feel safe, comfortable, caring and responsible for protecting children and the environment through healthy village activities. Based on the results of observations and interviews, it can show that empowerment of healthy villages in Margorejo is very dynamic and orderly. This is evidenced by the number of healthy village programs that are implemented in order to create a village environment that is conducive to children's growth and development and education.